The Vitruvian Man of Leonardo da Vinci as a model of innovative entrepreneurship at the intersection of business, art and technology - Mariella C. Remund; Marta Peris-Ortiz; Hans-Jurgen Gehrke (Journal of Innovation and Entrepreneurship, 2017)
The vital role of entrepreneurship for economic growth and its impact for job creation in mature and developing economies is widely recognized and quantified (OECD, Entrepreneurship and Business Statistics, 2015). According to Get2growth data (How Many Startups Are There?, 2015), 100 million start-ups are created each year of which 1.35% are technology-based companies, and according to the Kauffman Index of Entrepreneurial Activity (Fairlie, 2013), almost a quarter of new businesses in the USA were started by entrepreneurs aged 55 and older. Survival following failure data for start-ups are numerous and complex in the interpretation, and data presented by the Statistic Brain (Startup business failure rate by industry, 2015) show a 55% failure rate within the fifth year. Entrepreneurship is important for growth but sustainable entrepreneurship is hard to achieve. This paper, by means of a case study of a German private art museum 'Kunstmuseum Gehrke-Remund', analyzes the disruptive methods, both atypical and contrary to the mainstream art industry, developed to ensure the sustainable success of such an innovative endeavor. Our analyses and results contribute to the understanding of the building blocks and roadmap designed by the Kunstmuseum to successfully enter the elitist contemporary art industry, as an outsider, and provide an early indication that such methods can be theoretically replicated in other industries by other entrepreneurs.
Keywords: 650; Entrepreneurship; Disruptive innovation; Start-up; Art; Contemporary art; Business; Technology; Art museum; Private museums; Kunstmuseum Gehrke-Remund; Vitruvian man; Sustainable growth; Business model; Value creation; Experience map; Perfect execution; Creativity; Minimum viable product